Borderland Mystery and Tibetan Writing: On Ma Yuan’s Non-linear Spatial Narrative Strategy in Tibetan Novels - Long, Yingsu; Chsing Chsing, Lim (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
In the 1980s, Ma Yuan, as a literary explorer, carried out the pioneering art of literature and art with full enthusiasm for the life in Tibet, and devoted himself to creating a series of literary works with Tibet as the background. Currently, Ma Yuan’s Tibetan novels depict in depth the invaders and guardians of Tibetan national culture as well as the spread and development of Tibetan national culture, depicting the profound mystery and broad inclusiveness of Tibetan culture. His works are not only unique in form, fully reflecting the innovative qualities of pioneer novels, but also innovative in content, skillfully integrating the avant-garde nature of form and content. This paper mainly discusses how Ma Yuan’s non-linear spatial narrative strategy reveals the charm of the secret borderland, and summarizes the cultural implications reflected in Ma Yuan’s Tibetan novels’ narrative strategy, aiming to promote the dissemination and development of Chinese Tibetan novels